Research on the Construction of Cu2O Photonic Crystals on Different Textile Substrates and Their Mechanical Properties - Chunxing Zhou; Zhen Yin; Yiqin Shao; Guocheng Zhu; Parpiev Khabibulla; Adkhamjon Gafurov; Juramirza Abdiramatovich Kayumov (Textiles)
Structural color-generating materials are expected to replace pigments and dyes as a new type of color-developing materials with good light stability and bright colors. Due to the relatively high refractive index of Cu2O microspheres, they have strong Mie scattering in the visible region. Herein, various sizes of Cu2O microspheres were synthesized by a two-step reduction method, and the Cu2O spheres were firmly bonded to the fabrics by using the PVA binder. Four different fabrics (cotton, silk, polyester, and nylon fabrics) were evaluated to investigate the physical properties and color fastness. It turns out that the tensile and tearing properties of the Cu2O structured fabrics decreased to a certain extent, and the bursting properties of fabrics increased, except for the cotton structured fabrics. Meanwhile, all the structural colored fabrics showed excellent color fastness to shearing, rubbing, and washing. This study provides experimental data for developing the application of structural colors on different fabrics.